Las recientes reformas penales en Colombia: un ejemplo de irracionalidad legislativa (2007)
In view of the particularities of the social and political reality in Colombian, there are presented in the text some facts, statistics or records of the criminality in the country. It is underlined how the situation of internal conflict its manifest in a